PERLINDUNGAN KECELAKAAN KERJA TERHADAP PEKERJA MAGANG DI PT. BAKRIE TOSANJAYA MENURUT UNDANG – UNDANG NOMOR 3 TAHUN 1992 TENTANG JAMINAN SOSIAL TENAGA KERJA (JAMSOSTEK) - Sheren Diandra, Denise; Putrawan, Suatra (Kertha Semaya : Journal Ilmu Hukum, 2013)
In a corporation, employee is one of the most important assets, so the corporation is must be to provide for the protection and safety of employees and their families. The protection provided that is social security rights of employees. This protection based on Undang-Undang Nomor 3 tahun 1992 Tentang Jaminan Sosial Tenaga Kerja. But, it should be researched and examined further whether the legal instrument has been implemented and applied effectively and correctly. The goal of this journal to knowing how the legal protection for apprentices in PT. Bakrie Tosanjaya in the occurrence of accidents.
Keywords: Apprentices, Social security rights of employees